Carbon dots modified mesoporous organosilica as an adsorbent for the removal of 2, 4-dichlorophenol and heavy metal ions1. Issue 25 (7th July 2015) - Wang, Lingzhi; Cheng, Chen; Tapas, Sen; Lei, Juying; Matsuoka, Masaya; Zhang, Jinlong; Zhang, Fan
<x xml:space="preserve">Abstract</x> Carbon dot modified mesoporous silica is applied to the efficient removal of both organic and inorganic contaminants.